Impact of irrigation management on crop water footprint reduction using RZWQM2 in Baghdad, Iraq - Shahadha, Saadi Sattar; Mukhlif , Muneam K.; Salih, Riyadh M. (Journal of Aridland Agriculture, 2023)
Water scarcity becomes a serious global challenge in several world regions and particularly in the Middle East. Appropriate irrigation practice is critical for improving crop yield and alleviating crop water footprint (WF). To alleviate water scarcity, the possibility of reducing wheat and barley water footprint has been examined through alternative surface irrigation practices. The WF was compared under farmers’ irrigation practice and experimental irrigation practice to discover the impact of irrigation practices on the reduction of WF in the west of Baghdad. Weather data and crop management information were collected from 2016 to 2020 for the farmer’s fields in the study area as well as for the experimental field. The Root Zone Water Quality Model (RZWQM2) was used for estimating wheat and barley evapotranspiration. The study results showed that the crop WF was well estimated using the RZWQM2 due to the model capability and accuracy for estimating the impact of field management on crop evapotranspiration and crop water use. Experimental irrigation practice could improve crop yield, water use efficiency, and water profitability by up to 28%, 35%, and 35%, respectively; while the WF was reduced by 35%, compared to the farmers’ irrigation practice. The WF of the wheat crop was lower than the barley WF due to the low barley production.